La refonte permanente des lois du Québec : implications et modalités - Le May, Denis (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1977)
The purpose of this paper is to examine the implication and details of the consolidation of the statutes of the Province of Quebec which is now under way. Unlike earlier consolidations, this one will be permanent and brought up to date annually, and as he approaches his subject, the author describes what must be understood by keeping up to date and who should be responsible for the task. Next, he discusses the technical aspects which ought to be considered in the process of keeping the consolidation up to date, among which are the moment and methods to inserting new texts, the numbering of sections, and the vehicle for the publication of amending legislation. In the third part of his paper, the author describes what important changes would have to be made to the present situation, should the proposed system be adopted. These changes are both documentary (a new presentation of the Quebec official Gazette is advocated) and legislative (new duties of the Quebec Official Printer are stressed). Finally there is established a link between the permanent consolidation and a policy for non-official consolidations. The author concludes with the expression of a point of view on the access of the people to the law.